Exotic pediculosis and hair-loss syndrome in deer (Odocoileus hemionus) populations in California. (July 2016) - Roug, Annette; Swift, Pamela; Puschner, Birgit; Gerstenberg, Greg; Mertins, James W.; Johnson, Christine Kreuder; Torres, Steve; Mortensen, Jack; Woods, Leslie
Infestation with nonnative, "exotic" lice was first noted in Washington black-tailed deer ( Odocoileus hemionus columbianus ) in 1994 and has since then spread throughout the western United States. In California, infestation with the exotic louse Damalinia ( Cervicola ) sp. was first detected in black-tailed deer from northern California in 2004, and, in 2009, the exotic louse species Bovicola tibialis and Linognathus africanus were identified on mule deer ( Odocoileus hemionus californicus ) in central Sierra Nevada in association with a mortality event. Exotic lice have since been detected in various locations throughout the state. We describe the geographic distribution of these exotic lice within California, using data from 520 live-captured and 9 postmortem-sampled, free-ranging mule deer examined between 2009 and 2014. Data from live-captured deer were used to assess possible associations between louse infestation and host age, host sex, migratory behavior, season, and blood selenium and serum copper concentrations. Damalinia ( Cervicola ) sp. and B. tibialis lice were distinctively distributed geographically, with D. ( Cervicola ) sp. infesting herds in northern and central coastal California, B. tibialis occurring in the central coastal mountains and the Sierra Nevada, and L. africanus occurring only sporadically. Younger age classes and low selenium concentrations were significantly associated with exotic louse infestation, whereas no significant relationship was detected with serum copper levels. Our results show that exotic lice are widespread in California, and younger age classes with low blood selenium concentrations are more likely to be infested with lice than older deer.